Mapping and placemaking from the perspective of cultural field: The three historic sites of the western Han Dynasty in Hanzhong - Chen, Chao; Ren, Yunying (International Planning History Society Proceedings, 2018)
Recently, in the context of China's policy of vigorously developing the assertive culture confidence, the value of traditional culture has been re-recognized by the whole society. However, due to the unbalanced development of China's eastern and western regions, the value of cultural heritage is not valued in the western region. Hanzhong district in Shaanxi province, belonging to the intersection of the south and north, has its own unique natural and cultural environment. The three historic sites of the western Han Dynasty are located in the city centre of Hanzhong, and as the historical heritage of Han culture, it has been hesitant between protection and development for many years. On the one hand, this paper tries to introduce the concept of "field" into the protection of cultural heritage, by constructing the cultural field model and using the cultural field to explore the question of historical heritage activation. This article, on the other hand, by expanding the mapping function, using the method of mapping defined the three historic sites of the western Han dynasty culture field research scope and the elements, combing extracted place identity, controlling the space boundary of place and for placemaking, and proposing an operable strategy and approach.